Mapping the needs of healthcare workers caring for COVID-19 patients using the socio-ecological framework: a rapid scoping review - Konstantinou, Pinelopi; Theofanous, Vaso; Karekla, Maria; Kassianos, Angelos P. (My University, 2024)
Undoubtedly, the mental health of healthcare workers (HCWs) was negatively affected because of caring for patients during the COVID-19 pandemic. However, literature is limited on mapping the challenges and needs of HCWs during COVID-19 pandemic. A widely used framework in public health for mapping evidence includes the socio-ecological models, suggesting behavior can be influenced by individual, interpersonal, organizational, and community factors. The aim of this rapid scoping review was to use the socio-ecological model to map and compile lessons learnt from the literature regarding primarily the challenges and needs and secondly available psychological interventions for HCWs caring for COVID-19 patients. PubMed, CINAHL and Scopus databases were searched, with 21 studies finally included examining challenges and needs of HCWs and 18 studies presenting psychological interventions. Organizational-level challenges and needs such as inadequate staff preparation and supplies of protective equipment, flexible work policies and paid rest periods were the most reported. Individual-level challenges and needs included COVID-19-related fears and reduced mental health, whereas interpersonal-related needs included support provision. Community-level challenges included societal stigma. Certain psychological interventions were found to be promising for HCWs, but these were utilized to address only individual-level challenges and needs. Given that well-being entails an interaction of factors, multi-level interventions addressing multiple socio-ecological levels (interpersonal, organizational, community) and that place HCWs in their social context should be administrated to increase and maintain intervention' effects long-term and possibly aid in better coping with future pandemics.
Keywords: Socio-ecological models; COVID-19; Challenges; Healthcare workers; Needs; Psychological interventions